Integration of Bangla script recognition support in OCRopus - Chowdhury, Muttakinur Rahman (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.